The miRNA-29b Is Downregulated in Placenta During Gestational Diabetes Mellitus and May Alter Placenta Development by Regulating Trophoblast Migration and Invasion Through a HIF3A-Dependent Mechanism - Sun, Da-Guang; Tian, Shi; Zhang, Lu; Hu, Yi; Guan, Chun-Yi; Ma, Xu; Xia, Hong-Fei (Frontiers in Endocrinology, 2020)
Gestational diabetes mellitus (GDM) is a disease that changes the function of microvascular of placenta. MicroRNA (miRNA) expression in placenta may contribute to the pathogenesis of GDM. Here, we evaluate the role and function of miR-29b in the development of GDM. This study discovered that miR-29b expression was lower in placentas derived from patients with GDM than that in control placentas. MiR-29b over-expression inhibited cell growth and migration, and miR-29b knockdown promoted cell migration. Then we predicted and confirmed that HIF3A was a direct target of miR-29b with two specific binding sites at the recognition sequences of miR-29b in 3'-UTR of HIF3A mRNA, which was negatively correlated with miR-29b expression level. The up-regulation of HIF3A partially antagonized the inhibitory effect of miR-29b over-expression on cell growth and migration. The enhancement of cell migration induced by miR-29b knockdown was attenuated by down-regulating HIF3A. These results imply that down-regulation of miR-29b may be related with the development of GDM partially via increasing the expression of HIF3A, which may provide a new insight for the mechanism of GDM.